Effectiveness of Mother Tongue Instruction on Literacy Rates in Primary Education in Kenya, Examining the Transition from Indigenous Languages to English in Urban and Rural Settings - Muchemi, Joan (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to analyze the effectiveness of mother tongue instruction on literacy rates in primary education in Kenya, examining the transition from indigenous languages to English in urban and rural settings Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies on the effectiveness of mother tongue instruction in Kenya's primary education reveal that using indigenous languages in early education significantly improves literacy rates, particularly in rural areas. In these settings, children who learn in their native languages during the early grades develop stronger foundational literacy skills compared to those taught in English from the start. Unique Contribution to Theory, Practice and Policy: Sociocultural theory, cummins’ linguistic interdependence theory & transitional bilingual education theory may be used to anchor future studies on the effectiveness of mother tongue instruction on literacy rates in primary education in Kenya, examining the transition from indigenous languages to English in urban and rural settings. Schools, particularly in rural areas, need more resources like textbooks and teaching aids in indigenous languages to support early literacy development. Policymakers should implement flexible language policies that consider the different linguistic needs of urban and rural populations.